PENGARUH MOTIVASI KERJA, PENGALAMAN MENGAJAR DAN LINGKUNGAN KERJA TERHADAP PROFESIONALISME GURU TEKNIK OTOMOTIF SMK DI KABUPATEN WONOSOBO TAHUN PELAJARAN 2014/2015 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The reasearch aims to determine how much influence the work motivation, teaching experience and working environment either jointly or individually in the Automotive Engineering teacher’s professionalism at Vocational High School in Wonosobo regency Academic Year 2014/2015This reasearch uses a quantitative approach with a descriptive correlational research design . The variables in this study is the professionalism of teachers as the dependent variable , while the independent variable is the motivation to work , teaching experience , and the work environment . The data revealed by Automotive Engineering teachers at Vocational High School in Wonosobo regency totaling 73 people spread across 11 vocational schools either public or private status . The data were obtained by using a questionnaire instrument with closed questions. Data analysis technique used is multiple regression analysis for the influence jointly and partial correlations for the effect of partiallyFrom the results, (1) There is a significant influence of the work motivation, teaching experience and working environment on the automotive engineering teacher’s professionalism at Vocational High School in Wonosobo regency academic year 2014/2015 which influence the effectiveness of 59.6 % (2) There is a positive and significant influence of the work motivation on the automotive engineering teacher’s professionalism at Vocational High School in Wonosobo regency academic year 2014/2015 which influence the effectiveness of28.281 %, (3) There is a positive and significant influence of teaching experience on the automotive engineering teacher’s professionalism at Vocational High School in Wonosobo regency academic year 2014/2015 that influence the effectiveness of 21.040 %. (4) There is a positive and significant influence of the work environment on the automotive engineering teacher’s professionalism at Vocational High School in Wonosobo regency that influence the effectiveness of 11.840 %.